PENERAPAN PENDEKATAN KOMUNIKATIF DALAM PEMBELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN KETERAMPILAN BERBICARA PADA SISWA KELAS V.A DI MI MA’ARIF NU KALISALAK - Oky Prasetiyowati (Tamilis Synex: Multidimensional Collaboration, 2024)
The problem in this study is the low speaking skills of students in class V. A at MI Ma'arif NU Kalisalak. The purpose of this study was to determine the process of implementing a communicative approach in learning Indonesian to improve speaking skills in class V.A students at MI Ma'arif NU Kalisalak. To determine the factors that influence the implementation of a communicative approach in learning Indonesian to improve speaking in class V.A students at MI Ma'arif NU Kalisalak. The method used in this study is to apply a communicative approach in learning Indonesian. This type of research is Classroom Action Research which is carried out in 2 cycles, each cycle consisting of 3 meetings carried out with 4 stages, namely: Planning, Implementation, Observation and Reflection. Techniques in collecting data from Test results, observation of student and teacher activities. The results of the study from data analysis that in the Completeness of student learning outcomes in the Pre-cycle only 8 people (38.09%) completed, in cycle I increased to 14 people (66.67%) who completed and in cycle II increased to 21 people (100%) with a very good category, from these data it can be seen that speaking skills in learning Indonesian in class V.A students at MI Ma'arif NU Kalisalak Increased.